GENDER AND SUSTAINABILITY IN OVACIK AND HOZAT COOPERATIVE ACTIVITIES, TUNCELI PROVINCE, TURKEY - Öner, İlknur (Taylor and Francis, 2022)
Discussions on the promotion of gender equality, sustainability, income-generating activities, empowerment, resilient community development, and ecological approaches have improved in time. Thus, strengthening capacities and initiatives at the local level: delivering training, participation, business development provisions support, policy preparation empowerment, networking with prospective investors, initiators, and participants; marketing support provisions and collective activities have drawn attention to gender group activities. However, important points remain such as networking activities of men and women; the need for local, national, and international co-operation; and their interplays in existing or newly emerging structures. This paper is concerned with these missing points by examining how two types of income-generating activities of the two earliest cooperatives (agricultural activities-Ovacık and knitting dolls-Hozat) place gender groups in Hozat and Ovacık townships of Tunceli province in Turkey. Moreover, how intergroup dynamics and relationships among members and communities in their specific environments shape operations and, how the participants of these activities respond to the processes of such activities. The preliminary qualitative analysis acknowledges that women and men are treated differently both within the embedded activities interactions and responses with cultural, social, political, ecological, economic, and other settings. These are the remaining frame of several UN Sustainable Development Goals which are numbered 2, 5, 10, 11, 12, 13, 15, 16, and 17. Therefore, the sustainability and survival of these cooperatives and the promotion of their activities require close multidisciplinary scrutinization and multifactoral support. For this, the vision of understanding networks without segregation is necessary to strengthen social relationship areas and lines. © 2023 selection and editorial matter, Astrid Skjerven and Maureen Fordham; individual chapters, the contributors. All rights reserved.